Culture of diatom Culture of diatomusing oil palm waste as live food for harpacticoid copepod and black tiger shrimp postlarvae - Enche Baharuddin, Ninie Noor Diana (2023)
Malaysia is one of the world’s largest producers and exporters of palm oil, accounting for roughly one-third of global production. Palm oil mill effluent (POME) and Palm oil fuel ash (POFA), two types of oil palm waste that are produced in large quantities by palm oil milling activities, pose significant environmental risks and are considered serious environmental polluters in Malaysia. Alternatively, POME and POFA may provide prospects for diatom growth and extraction of high-value products due to their high nutrient and silica levels. The goal of this study was to develop marine benthic diatom Halamphora sp. culture exploiting POME and POFA for the enrichment of harpacticoid copepod Amphiascoides neglectus and black tiger shrimp Penaeus monodon postlarvae culture. This study showed that Halamphora sp. can be grown effectively with and without substrate, and PVC substrate is a viable alternative. It was found that the ideal growth parameters for Halamphora sp. include the photoperiod (light/dark) of 12:12 h to 18:06 h; light intensities of 80 to 120 μmol m−2 s−1; salinities of 30 to 35 ppt; and pH of 8 to 9. The results revealed that higher Halamphora sp. growth can be obtained when cultured with 15% POME compared to the commercial medium, f/2 + Si (control). The microalga could also reduce the ammoniacal nitrogen, nitrate, nitrite, and orthophosphate levels in the POME concentrations of 5% and 15%. Meanwhile, there was no significant difference (P > 0.05) between the growth of Halamphora sp. added with 50%, 75%, and 100% of POFA as the silica sources. In the feeding experiment, the addition of Halamphora sp. for harpacticoid copepod enrichment led to higher nutritive values of the zooplankton and maintains the culture water quality between the acceptable ranges with zero water exchange. Furthermore, the addition of Halamphora sp. and enriched harpacticoid copepod improved the survival and nutritional content of the Penaeus monodon postlarvae compared to the control treatment. The addition of both consortia also protected the postlarvae from Acute Hepatopancreatic Necrosis Disease causing Vibrio parahaemolyticus. This study could pave the way for future research on using oil palm waste to culture beneficial microalgal biomass for aquaculture purposes.